2017
DOI: 10.1002/mus.25629
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance myography in individuals with collagen 6 and laminin α‐2 congenital muscular dystrophy: a cross‐sectional and 2‐year analysis

Abstract: Introduction: Electrical impedance myography (EIM) is a noninvasive electrophysiological technique that characterizes muscle properties through bioimpedance. We compared EIM measurements to function, strength, and disease severity in a population with congenital muscular dystrophy (CMD). Methods: Forty-one patients with CMD, either collagen 6 related disorders (COL6-RD; n 5 21) or laminin a-2-related disorders (LAMA2-RD; n 5 20), and 21 healthy pediatric controls underwent 2 yearly EIM exams. In the CMD cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In FSHD we showed test–retest reliability of EIM variables and broad correlations with FSHD disease measures . Despite its increasing use in muscular dystrophies, what EIM is measuring in the muscle is not well understood. Magnetic resonance imaging quantitative intramuscular Dixon fat fraction (FF) and a T1‐based muscle severity score (T1 muscle score) are promising biomarker candidates for alterations in FSHD muscle structure.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In FSHD we showed test–retest reliability of EIM variables and broad correlations with FSHD disease measures . Despite its increasing use in muscular dystrophies, what EIM is measuring in the muscle is not well understood. Magnetic resonance imaging quantitative intramuscular Dixon fat fraction (FF) and a T1‐based muscle severity score (T1 muscle score) are promising biomarker candidates for alterations in FSHD muscle structure.…”
Section: Introductionmentioning
confidence: 79%
“…In congenital muscular dystrophy, EIM 50 kH Z phase was useful in tracking function and strength in ambulatory collagen VI patients but had no correlation with strength or function in the nonambulatory LAMA2 cohort . In Duchenne muscular dystrophy (DMD), EIM phase ratio showed a slope of decline steeper than traditional functional measures, likely reflecting the disease progression in muscles .…”
Section: Discussionmentioning
confidence: 97%
“…It is still unclear which EIM variables are best suited to measure changes, and the choice for a specific variable depends on the disease being studied. Consequently, multiple studies have used different outcomes including, among others, single and multifrequency measures, single muscle and composite measures, single phase values, and phase ratios . Prior studies have shown that reactance is least susceptible to variability in subcutaneous fat content or electrode configuration .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, multiple studies have used different outcomes including, among others, single and multifrequency measures, single muscle and composite measures, single phase values, and phase ratios. 11,[13][14][15]25 Prior studies have shown that reactance is least susceptible to variability in subcutaneous fat content or electrode configuration. 26 Despite this, several studies have used phase ratios rather than reactance; this value appears to be optimized for function versus subcutaneous fat in muscle disease and, as a derived measure, uses both elements of reactance and resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation